Expanding a B2B brand into the B2C market: The case of Mistolin Solutions - Seco, Sofia Ferreira (2022)
The rise and spread of the internet have significantly impacted businesses, encouraging new activities and operations for companies, which can now more easily expand their business in terms of clients and geography. This research focuses on the case of the B2B company Mistolin Solutions, the largest Portuguese distribution network of professional hygiene and cleaning products, which aims to explore the possibility of expanding into the B2C market with the support of its online store. The general research objective is then to analyze the perception of the B2C market towards the online store of the brand. The study adopts a quantitative survey methodology, resorting to the questionnaire technique. A total of 138 valid responses were collected from end consumers. Findings demonstrate that, among the nine addressed independent variables, only perceived benefits and discount proneness significantly and positively influence the general interest of purchasing in the online store of the brand. Additionally, the kitchen, surfaces and pavements, and ecological products categories were found to be the most attractive ones for end consumers. Lastly, end consumers general interest in buying from Mistolin Solutions online store proved to not be significant enough.